2010
DOI: 10.3189/002214310794457254
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of alpine subglacial lakes using interferometric synthetic aperture radar (InSAR): Brady Glacier, Alaska, USA

Abstract: The temporary storage and subsequent release of water at glacial margins can cause severe flooding in downstream areas and substantially impact glacier dynamics. Alpine subglacial lakes may not be identified until they become subaerially exposed or release a jö kulhlaup. We use interferometric synthetic aperture radar (InSAR) to identify and characterize three dynamic alpine subglacial lakes of Brady Glacier, Alaska, USA. We quantify changes in vertical displacement of the glacier surface and lake volumes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…InSAR provides avenues to study glaciers in terms of snout and glacial lake monitoring, as well as ground displacement and topographic variations, using interferograms (Luckman, Quincey, and Bevan 2007;Kumar et al 2008;Capps et al 2010). Glacier monitoring using InSAR is advancing towards new frontiers; in this study, we develop coherence maps using SAR image pairs to map the location of the snout of the Gangotri glacier.…”
Section: Coherence Detection For Glacier Retreatmentioning
confidence: 99%
“…InSAR provides avenues to study glaciers in terms of snout and glacial lake monitoring, as well as ground displacement and topographic variations, using interferograms (Luckman, Quincey, and Bevan 2007;Kumar et al 2008;Capps et al 2010). Glacier monitoring using InSAR is advancing towards new frontiers; in this study, we develop coherence maps using SAR image pairs to map the location of the snout of the Gangotri glacier.…”
Section: Coherence Detection For Glacier Retreatmentioning
confidence: 99%
“…In the past decade, research has confirmed that glacier-dammed lakes and jökulhlaups can ice-dammed lakes (Larsen, et al, 2007;Capps et al, 2010). Six of the ten lakes are primarily subaerial (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Based on the results of this study and the conclusions reached by Capps et al (2010), these lakes will become increasingly subaerial if Brady Glacier continues to downwaste and retreat, especially as the calving fronts increase in width and depth, thereby creating a positive feedback cycle for more ice loss. Oscar Lake recently began a rapid subaerial expansion.…”
Section: Space As a Proxy For Timementioning
confidence: 99%
See 1 more Smart Citation
“…Glacial lakes are important indicators of the regional glacier dynamics in response to climate warming and changing precipitation [1][2][3]. With the continuous retreating and thinning of mountain glaciers in the Tibetan Plateau, a large number of glacial lakes have developed and experienced rapid expansion in recent decades, leading to the increased hazard risk of glacial lake outburst floods (GLOFs) [4].…”
Section: Introductionmentioning
confidence: 99%